Evaluating the impact of business incubators on promoting growth and creativity in women’s projects in Jordan - AlBataineh, Abdel Karim Fawwaz; Harb, Ayman Saleh Mustafa; Alnajjar, Ahmad Hisham; Alhaj, Read Shawkat (International Journal of Management and Sustainability, 2024)
The goals of the vision included economic modernization and, based on the royal directives, the necessity of doubling Jordanian women’s participation in the labor market, not in order to improve the annual growth rate but in order to invest in achieving gender parity with economic participation and women’s empowerment. Despite the presence of many obstacles to achieving this, the Jordanian government has legislated laws that help remove these obstacles, but they still need to be activated at the level of all activities, including equality between wages between males and females, etc. The study concluded with the necessity of activating the role of business incubators to empower women’s economic, political, health, educational, etc. role, with the necessity of investment and equality in the use of human capital, especially females, after rehabilitation and training, especially in the areas where women live, in order to achieve growth and creativity. The focus is on academic education only; it led to an increase in the unemployment rate among females in Jordan, and this helped them migrate from villages to the city in search of a better job opportunity. Therefore, the government’s intention to transform education into two tracks: academic, vocational, and industrial, will give women an incentive to enter into a new challenge and give them an opportunity for creativity through coordination with business incubators to develop entrepreneurial projects and enable women to achieve sustainable development.